Surveillance of adult Aedes mosquitoes in Selangor, Malaysia. Issue 10 (14th July 2015) - Lau, Sai‐Ming; Vythilingam, Indra; Doss, Jonathan Inbaraj; Sekaran, Shamala Devi; Chua, Tock H.; Wan Sulaiman, Wan Yusof; Chinna, Karuthan; Lim, Yvonne Ai‐Lian; Venugopalan, Balan
Abstract Objective To determine the effectiveness of using sticky traps and the NS1 dengue antigen kit for the surveillance of Aedes mosquitoes for dengue control. Methods Apartments were selected in a dengue‐endemic area, and sticky traps were set to capture adult Aedes mosquitoes. NS1 dengue antigen kit was used to detect dengue antigen in mosquitoes, and positive mosquitoes were serotyped using real‐time RT‐PCR. Results The sticky traps were effective in capturing Aedes aegypti, and a minimum of three traps per floor was sufficient. Multiple serotypes were found in individual mosquitoes. Conclusion The sticky trap and the NS1 dengue antigen test kit can be used as surveillance tool in dengue control programmes. This proactive method will be better suited for control programmes than current reactive methods.